The Conception of Morality and Value Education In Islamic Education - Sudirman, Sudirman (Jurnal Simki Pedagogia, 2023)
This article discusses the conception of morality and value education in Islamic education. The method used in writing this article is library research where the source comes from books and journals. From the information that has been obtained, it can be concluded that morality is a moral trait or overall principles and values relating to good and bad. Morality is basically the same as morality which adheres to good or bad values and norms. Values education as an aid to students to realize and experience values and place them integrally in their whole lives. This value education is not only a special program that is taught through a number of subjects, but also includes the entire educational process. Islam views value or moral education as the core of education itself. The Islamic religion is based on the Al-Qur'an and Hadith. Therefore, we can understand that moral education in the teachings of Islamic education plays an important role in the effort to create a complete human being or perfect human being.